From file to print - Manuel Ferreiro Ardións; Juan Lezaun Valdubieco (Universidad de Alicante, 2017)
This editorial contains some experiences accumulated in the process of elaboration and publication of the book on the History of Nursing entitled Maese Francisco de Herrera, un barbero-cirujano en la peste de 1599 en Vitoria.